Definicja dokumentu w kryminalistyce a dokument (i podpis) elektroniczny - Taracha, Adam (Wydawnictwo Uniwersytetu Wrocławskiego. Wydawnictwo "Szermierz" sp. z o.o., 2023)
The study presents the issues related to the appearance of a new category of evidence in the Polish legal system – electronic evidence. The author discusses the scope of such terms as document (in terms of forensics and penal proceedings), electronic document and electronic signature. It indicates the changes in legal transactions caused by the introduction of electronic documents (including a significant reduction in the occurrence of handwritten signatures). He notes that the definitions of the document in the Polish forensic literature have remained unchanged for years. The work ends with a proposal for a new, extended definition of a document, which covers all ways of transmitting the conceptual content (graphic, acoustic), as well as the forms of its recording (analog or digital).
Keywords: document; audio document; handwritten signature; electronic document; electronic signature